Falls in systolic blood pressure during dialysis which require no nursing intervention are associated with increased patient intra-dialytic symptom self-reporting and prolonged post-dialysis recovery times - Suree Yoowannakul (2020)
© 2020 The Author(s). Background: Haemodialysis (HD) patients may suffer symptoms during dialysis and take time to recover post HD. We wished to determine whether patients with symptomatic intra-dialytic hypotension (IDH), requiring nursing interventions, or an asymptomatic fall in systolic blood pressure (SBP) reported more symptoms during dialysis. Methods: Six hundred three HD patients completed self-reported intra-dialytic symptom questionnaires and recovery using a visual analogue scale, which were compared with their dialysis session records. Results: Twenty-nine (4.8%) of patients suffered symptomatic IDH, and 187 (31.0%) had a fall in SBP of > 20 mmHg. Symptomatic patients had greater total symptom scores (30 (23-44) vs 23 (10-38), p < 0.05, versus asymptomatic patients, with increased low blood pressure, dizziness, cramps, palpitations and feeling cold reported (all p < 0.05). Patients with a SBP fall of > 20 mmHg had greater total scores compared with those with a SBP increase of > 10 mmHg (26 (13-38) vs 17 (7-34), p < 0.05), with more dizziness, cramps, backache, shortness of breath and headache reported (all p < 0.05). Although ultrafiltration rates were similar, HD weight loss was greater for patients with a SBP fall of > 20 mmHg (2.5 ± 1.1 vs 2.0 ± 1.3%, p < 0.05). Patients with highest symptoms scores (highest vs lowest quartile) had longer recovery times (40.3 vs 7.6% > 4 h), p < 0.001. Multivariable analysis showed that patients reporting more intradialytic symptoms had higher psychological distress thermometer scores (odds ratio (OR) 1.34 (95% confidence limits 1.26-1.44)), systolic blood pressure < 100 mmHg (OR 2.53 (1.04-6.1)), whereas symptom scores were lower for male gender (OR 0.34 (0.22-0.51)), and with increasing age (OR 0.99 (0.97-0.99)). Conclusion: Patients with both symptomatic and asymptomatic IDH, self-reported more symptoms during dialysis, and those patients reporting more symptoms had longer recovery times. We found that younger, female patients, those with greater psychological distress, and lower systolic blood pressure self-reported more intra-dialytic symptoms. More attention is required to prevent falls in intra-dialytic blood pressure to improve the patient experience of HD and shorten post-dialysis recovery times.